INTERNET BUSINESS MODELING: DEVELOPMENT OF INFORMATION INFRASTRUCTURE, TECHNOLOGIES, AND MODELS - Gasparian, Mikhail Samuilovich; Kiseleva, Irina Anatolievna; Chernysheva, Elena Nikolaevna; Androshina, Irina Sergeevna (Compusoft: an international journal of advanced computer technology, 2020)
Modeling the activities of Internet companies, the main task of which is to conduct an effective business, is explored in this article. The Internet faces such problems as the issue of privacy and security of the information transmitted, the issue of insufficient access to the web in some parts of the world, and some technical issues in such a seemingly high-tech system. As long as there is an Internet business, this topic will always be relevant. The need to combine optimal information systems with models of interaction between users is a constant problem that researchers, business, and government agencies are trying to find a solution. Each of the participants in this process considers the situation from their own point of view. However, the achievements of all parties form one or another model that determines the development of information systems and technologies. The models of the information business are analyzed, the directions of information commerce and the factors for the effective implementation of business models and the attractiveness of the Internet market are considered in the article. The choice of topic is determined by international trends aimed at developing business with minimal barriers for consumers in terms of receiving goods or services. In particular, during the period of struggle with COVID-19, when people are forced to stay at home, those companies that are poorly represented on the Internet will not be able to achieve success in their work. However, without the development of an optimal information infrastructure, software and sites, technologies and models, it is impossible to ensure fast customer acquisition and service.